1996
DOI: 10.1192/bjp.168.5.571
|View full text |Cite
|
Sign up to set email alerts
|

Idazoxan and Response to Typical Neuroleptics in Treatment-Resistant Schizophrenia

Abstract: The antagonism of alpha 2 receptors augmented therapeutic response to typical neuroleptic treatment in treatment-resistant patients with schizophrenia. This antagonism may contribute to clozapine's superior antipsychotic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
61
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(67 citation statements)
references
References 18 publications
6
61
0
Order By: Relevance
“…104 Indeed, combined treatment of a selective a 2 adrenergic receptor antagonist with a typical antipsychotic drug has been reported to produce a profile of antipsychotic activity similar to clozapine. 105 Thus, balancing a 2 adrenergic receptor activity to achieve both antipsychotic and pro-cognitive efficacy may be challenging.…”
Section: Serotonin 5-ht 4 Receptorsmentioning
confidence: 99%
“…104 Indeed, combined treatment of a selective a 2 adrenergic receptor antagonist with a typical antipsychotic drug has been reported to produce a profile of antipsychotic activity similar to clozapine. 105 Thus, balancing a 2 adrenergic receptor activity to achieve both antipsychotic and pro-cognitive efficacy may be challenging.…”
Section: Serotonin 5-ht 4 Receptorsmentioning
confidence: 99%
“…Clozapine displays nanomolar affinity for the ␣ 2C adrenoceptor (K I 9.1 nM) and some se-lectivity relative to the ␣ 2A subtype (K I 50 nM) (Schotte et al 1996). It has been speculated that clozapine's superior therapeutic activity is at least partly explained by ␣ 2 -adrenoceptor blockade (Nutt 1994;Litman et al 1996;Hertel et al 1999). Other therapeutic effects of clozapine may also be related to ␣ 2 -adrenoceptor blockade.…”
Section: Affinity For ␣ 2a and ␣ 2c Adrenoceptorsmentioning
confidence: 99%
“…The elucidation of the multiple receptor interactions of clozapine suggested that other neurotransmitter systems may also play a role in the efficacy and tolerability of that molecule. Particularly, the antiadrenergic effects of clozapine are now receiving increased attention (Nutt 1994;Litman et al 1996;Hertel et al 1999). Iloperidone is a new psychotropic agent currently undergoing Phase III trials for the treatment of psychotic disorders (Figure 1).…”
mentioning
confidence: 99%
“…In some (Breier et al 1994b;Schulz et al 1997;Fleischhaker et al 1998), but not all (Brown et al 1997) studies, plasma NE increases have been related to clinical improvement, suggesting that this pharmacological effect may play a role in clozapine's beneficial central actions. In this context, findings implicating noradrenergic dysregulation in the pathophysiology of schizophrenia (Stein and Wise 1971;Sternberg 1984;Breier et al 1990;Rao and Moller 1994;Breier 1994;Yamamoto et al 1994;Litman et al 1996;Breier et al 1998;Goff and Evins 1998;Friedman et al 1999a;Friedman et al 1999b;Klimek et al 1999) further support inquiry into the relevance of noradrenergic mechanisms in the action of APDs.We have reported previous data suggesting that high plasma NE levels in clozapine-treated patients result from increases in the appearance rate of the endogenously released NE in the plasma (spillover) rather than from decreased neuronal uptake of NE, inhibition of intraneuronal monoamine oxidase (MAO), or adrenoceptor antagonism . Risperidone, the next atypical antipsychotic drug marketed in the United States after clozapine, is associated with a low incidence of EPS and may have improved efficacy compared with conventional agents (Kane and McGlashan 1995;Pickar 1995;Campbell et al 1999).…”
mentioning
confidence: 96%
“…In some (Breier et al 1994b;Schulz et al 1997;Fleischhaker et al 1998), but not all (Brown et al 1997) studies, plasma NE increases have been related to clinical improvement, suggesting that this pharmacological effect may play a role in clozapine's beneficial central actions. In this context, findings implicating noradrenergic dysregulation in the pathophysiology of schizophrenia (Stein and Wise 1971;Sternberg 1984;Breier et al 1990; Rao and Moller 1994;Breier 1994;Yamamoto et al 1994;Litman et al 1996;Breier et al 1998;Goff and Evins 1998;Friedman et al 1999a;Friedman et al 1999b;Klimek et al 1999) further support inquiry into the relevance of noradrenergic mechanisms in the action of APDs.…”
mentioning
confidence: 96%